Corporate social responsibility : an exploratory study of CSR landscape in Bang Tao Beach, Phuket. - Huang, Evonne Shu Qi. (2011)
To achieve sustainable tourism in a tourist destination, many hospitality companies have applied Corporate Social Responsibility (CSR). This research will focus on how attuned the beach resort Bang Tao Beach is to sustainability via CSR by identifying the stakeholders involved, analyzing their CSR initiatives, and their contributions to the resort’s CSR landscape. Results show that an affiliation with a CSR-driven integrated resort has a beneficial influence on CSR engagement by stakeholders, and there are substantial differences between CSR undertaken by an integrated and independent hotels. Stakeholders include Tourists, the Local Thai Community, Hotel Operators, Non- Profit Organizations, Phuket’s Municipal Government and Advocates. Interactions amongst stakeholders via the roles of a ‘Motivator’ and ‘Facilitator’ were found to be integral to Bang Tao Beach’s CSR landscape development. As the CSR landscape was found to be at its infancy stage and hence less able to contribute significantly to Bang Tao Beach’s sustainability, recommendations for improvement include increasing stakeholders’ level of awareness so that their CSR initiatives can be better aligned towards issues that have a positive impact on Bang Tao Beach’s sustainable tourism.